Evidence of Proof in the Administrative Investigation and Employee Guarantees Towards it : A Comparative Study - Salim, Sultan; Bader, Ameera (Journal of Legal Sciences, 2023)
The aim of this research is to identify the guarantees of collecting evidence in the administrative investigation in both the Federal Decree-Law No. (11) of 2008 regarding human resources in the federal government and its amendments, and Ministerial Resolution No.(1) of 2018 regarding the executive regulations of the Human Resources Law in the Federal Government, Compared to the Jordanian Civil Service System No.(9) for the year 2020. In order to find out the guarantees obtained by the employee to whom the job violation is attributed in order to confront the authority of the administration in the event that he is referred to the administrative investigation in the stage of collecting evidence. And to search for the balance between the legal position of the public employee and the authority of the administration at this stage of the administrative investigation.And this research relied on the comparative analytical method, and the research reached several results, the most important of which is that both the Emirati and Jordanian legislators did not put texts on disciplinary procedures. But both legislators contented themselves with listing some general provisions. And accordingly the authority can The competent administrative investigation - in order to reach the collection of evidence that leads to the formation of the conviction and belief of the disciplinary authority - to carry out all physical verification operations in order to reach a disclosure The reality of the functional violation, and the identification of its perpetrator. It also has the competent investigation authority to review, examine and inspect the documents, papers and administrative documents related to the committed violation.